Inhibition of Nischarin Expression Attenuates Rilmenidine-Evoked Hypotension and Phosphorylated Extracellular Signal-Regulated Kinase 1/2 Production in the Rostral Ventrolateral Medulla of Rats - Zhang, Jian; Abdel-Rahman, Abdel A. (East Carolina University, 2008)
Imidazoline (I1)-evoked hypotension is linked to enhanced phosphorylated extracellular signalregulated kinase (pERK)1/2 production in the rostral ventrolateral medulla (RVLM). Recent cell culture findings suggest that nischarin is a candidate for the I1 receptor. In the present study, nischarin antisense oligode-oxynucleotide (ODN) (AS1 or AS2), designed according to nischarin cDNA sequence, was administered intracisternally (i.c., 2 nmol/rat for 2 days) to knockdown central nischarin expression; control rats received the corresponding mismatched ODN (MM1 or MM2) or artificial cerebrospinal fluid (aCSF). We investigated the effects of AS1 or AS2 on nischarin expression in the RVLM, and on the hypotension and RVLM pERK1/2 production elicited by the I1-selective agonist rilmenidine (25 μ g/rat i.c.). Compared with aCSF, the mismatched ODN (MM1 or MM2) had no significant effect on RVLM nischarin expression or the cardiovascular and cellular (RVLM pERK1/2) responses elicited by rilmenidine. However, either antisense ODN substantially (>80%) reduced nischarin expression in the RVLM (AS1/MM1, 3 ± 1 versus 32 ± 2 positive cells; AS2/MM2, 4 ± 1 versus 31 ± 2 positive cells) and abrogated rilmenidine (I1)-evoked hypotension (AS1/MM1, −4.1 ± 0.9 versus −10.8 ± 1.9 mm Hg; AS2/MM2, −2.1 ± 1.1 versus −15.3 ± 2.5 mm Hg) and ERK1/2 activation in the RVLM (AS1/MM1, 10 ± 1 versus 15 ± 2 positive cells; AS2/MM2, 9 ± 1 versus 18 ± 2 positive cells). Finally, pERK1/2 generated by central I1 receptor activation is colocalized with nischarin in the RVLM neurons. This is the first evidence in vivo that nischarin plays a critical role in I1 receptor-mediated pERK1/2 production in the RVLM and the subsequent hypotension. Origianlly published Journal of Pharmacology and Experimental Therapeutics, Vol. 324, No. 1, Jan 2008
Keywords: Nischarin; Imidazoline evoked hypotension; Signal regulated kinase